Exploring the potential of a highly scalable metal-organic framework CALF-20 for selective gas adsorption at low pressure - Borzehandani, Mostafa Yousefzadeh; Jorabchi, Majid Namayandeh; Abdulmalek, Emilia; Abdul Rahman, Mohd Basyaruddin; Mohammad Latif, Muhammad Alif (MDPI, 2023)
In this study, the ability of the highly scalable metal-organic framework (MOF) CALF-20 to adsorb polar and non-polar gases at low pressure was investigated using grand canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulations. The results from the simulated adsorption isotherms revealed that the highest loading was achieved for SO2 and Cl2, while the lowest loading was found for F2 molecules. The analysis of interaction energies indicated that SO2 molecules were able to form the strongest adsorbent-adsorbate interactions and had a tight molecular packing due to their polarity and angular structure. Additionally, Cl2 gas was found to be highly adsorbed due to its large van der Waals surface and strong chemical affinity in CALF-20 pores. MD simulations showed that SO2 and Cl2 had the lowest mobility inside CALF-20 pores. The values of the Henry coefficient and isosteric heat of adsorption confirmed that CALF-20 could selectively adsorb SO2 and Cl2. Based on the results, it was concluded that CALF-20 is a suitable adsorbent for SO2 and Cl2 but not for F2. This research emphasizes the importance of molecular size, geometry, and polarity in determining the suitability of a porous material as an adsorbent for specific adsorbates.